Large‐Scale Carbon Dioxide Removal to Meet the 1.5°C Limit: Key Governance Gaps, Challenges and Priority Responses. (25th April 2021) - Mace, M.J.; Fyson, Claire L.; Schaeffer, Michiel; Hare, William L.
Abstract: Parties to the UNFCCC and Paris Agreement have agreed to pursue efforts to limit the global average temperature increase to 1.5°C. To meet this goal, the international community will have to aggressively reduce emissions and also remove CO2 from the atmosphere on an unprecedented scale, through an array of biological and technical Carbon Dioxide Removal (CDR) options. This paper considers governance challenges that arise from the need to rely on CDR to meet the Paris Agreement's long‐term temperature goal. It looks at how heavy this reliance may have to be, over what timeframe, involving what options and, crucially, how best to ensure that CDR does not, while trying to address one problem, create many other challenges for sustainable development. After identifying the potential scale and pace of CO2 removal needed to meet the 1.5°C goal, we identify key governance gaps and challenges that arise from large‐scale CDR implementation and propose a series of policy responses to be addressed by policy makers as a matter of priority, to enable CDR to contribute to 1.5°C‐consistent pathways at the scale and pace required. Abstract : If 2030 targets do not improve dramatically, the international community will need to rely heavily on CDR options that are as yet unproven at scale to meet the Paris Agreement's 1.5C temperature limit. Significant governance gaps and challenges will have to be addressed as a priority to enable CDR to contribute at the scale and pace required.